Impact of prolonged water‐gas flow on the performance of polyacrylamide. Issue 17 (13th December 2021) - Al‐Shajalee, Faaiz; Seyyedi, Mojtaba; Verrall, Michael; Arif, Muhammad; Al‐Yaseri, Ahmed Z.; Tadé, Moses O.; Wood, Colin; Iglauer, Stefan; Saeedi, Ali
Abstract: Excessive water production from natural reservoirs is a major challenge in oil and gas industry. Relative permeability modifiers (RPM) are used to selectively reduce water production with minimum effect on the hydrocarbon production. This work examined the performance of polyacrylamide in terms of its water control efficiency at prolonged water‐gas flowing cycles. During each cycle, as the volume of injected water increased, the RPM demonstrated stronger performance in terms of reducing water permeability. This is attributed to the swelling of polymer layer adsorbed to the pore surfaces. Conversely, during each cycle, higher volume of gas injection led to less reduction in the gas effective permeability ( PR g ) which is due to polymer shrinkage. The reduction in water absolute permeability ( PR w ) of the treated micromodel in each injection cycle was significantly greater than the reduction in gas permeability. Interestingly, as water‐gas cycles progressed, a significant increase in water permeability reduction was observed. It is also found that polymer expansion and shrinkage are reversible. As such, the RPM performance depends on the injected fluid, injected fluid volumes and water‐gas injecting cycling. We thus conclude that that polymer swelling, and shrinkage and polymer‐gas interaction play a vital role in RPM performance. Abstract :